Approach to comprehensive analysis of bastion castle ensemble with historic gardens: novel combined strategy - Olha Tikhonova (Vitruvio: International Journal of Architectural Technology and Sustainability, 2022)
Bastion castle ensemble is a complex structure that belongs to defensive residences, which usually include the historic gardens and play an important role in the formation of the townscape. The two main structural components of such built complexes are palatial body and bastion fortifications. However, some bigger ensembles can also include other functional buildings. Due to the nature of the structure, namely the presence of defensive elements, which followed military development, many bastion castles underwent huge transformations. They were built and rebuilt because of the outdated design or destruction by the enemy. That is why studying such ensembles only from a historical perspective or analyzing only their fortification part is not enough to understand the whole complex, which is much more than a single-type building. In contrast, this paper proposes an interdisciplinary approach to studying bastion castles on the example of a bastion castle in Zheshov (Poland). Specifically, this paper uses a combined strategy that includes interpretative–historical and qualitative-computational strategies as a systematic and comprehensive approach to the research. This strategy consists of seven points of analysis: historical transformations, composition, situation, landscape, fortifications, typomorphology, and space syntax. This work represents a methodological framework that can be used for the analysis of any bastion castle ensemble in the world.